2003
DOI: 10.1021/tx020049d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Identification of Prostanoid Inducible Proteins by LC-ESI-MS/MS and MALDI-TOF Mass Spectrometry

Abstract: Protein identification by MS is well-established. Mixtures of proteins from cell extracts are separated by either one- or two-dimensional gel electrophoresis, and specific bands or spots are subjected to in-gel digestion and subsequent analysis by MS. The two most common types of ionization used in MS are electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI). When ESI is used, the sample is typically analyzed by inline HPLC-ESI-MS/MS with fragmentation of individual digest pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The tryptic digests were analyzed on a Voyager-DE PRO matrix-assisted laser desorption/ionization time of flight MS (Applied Biosystems, Foster City, CA) as described previously (16,17) with minor modifications. The samples were desalted using a Ziptip -C18 pipette tip (Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The tryptic digests were analyzed on a Voyager-DE PRO matrix-assisted laser desorption/ionization time of flight MS (Applied Biosystems, Foster City, CA) as described previously (16,17) with minor modifications. The samples were desalted using a Ziptip -C18 pipette tip (Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…It was previously reported that MALDI-TOF and LC-MS/MS are equally efficient at protein identification when comprehensive databases are available (Lim et al, 2003;Person et al, 2003). With plant species such as B. napus, for which database resources are limited, application of both MS methods may improve the identification rate.…”
Section: Lc-ms/ms Yielded Higher Percentage Of Protein Assignments Thmentioning
confidence: 99%
“…In MALDI, almost all peptides are singly-charged, while in ESI longer peptides usually involve doubly or triply-charged. [64][65][66] Furthermore the ESI analysis includes only those peptides definitively identified via MS/MS fragmentation, whereas the MALDI identification is by mass alone. 64 In summary, we have analyzed proteins from rat brain synaptic vesicles using two different separation methods and mass analysis techniques, cRPLC/MS/MS and 2DE-MALDI-TOF/MS.…”
Section: Discussionmentioning
confidence: 99%